ANALISIS DAYA SAING DOSEN DALAM MENGHADAPI ERA MASYARAKAT EKONOMI ASEAN (Studi Kasus Dosen Fakultas Ekonomi pada PTS di Kota Palembang) - Pandriadi Pandriadi; Asma Mario (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This research aims to analyze the competitiveness of lecturer facing AEC era, a case study in Economic Faculty at some universities in Palembang City. The competitiveness is measured by four indicators namely ability of English, ability to get research funding, ability to get funding for community service and ability to publish articles in journal. Respondent in this research are 100 lecturers who work in some private universities in palembang City. They filled a questionnaire which contents information about their compentencies in four indicators. Based on the analysis, this research concludes that the competitiveness of respondent majority are low, because from 100 respondent, 94 have low competitiveness, 4 have middle competitiveness and zero high competitiveness. The researcher recommend that for increasing competitiveness, the university should hold a sustainable English training for lecturers and also gives funding support to lecturer for doing researchs and community services programs.